PENCIPTAAN BUKU POP-UP LEGENDA KETINTANG DENGAN MENGGUNAKAN TEKNIK MOVEABLE SEBAGAI UPAYA KONSERVASI BUDAYA LOKAL SURABAYA - Azizah, Fenny Tri Nur; Bahruddin, Muhammad; Budiardjo, Hardman (Jurnal Art Nouveau, 2016)
Abstract: The purpose of this Creation so that people in Surabaya, especially in the area know of the existence Legend of Ketintang. The creation of this book will use the qualitative method by conducting interviews, observation, and literature to obtain data to supplement and support in the creation of movable pop-up book about the legend of this Ketintang. The data that collected will be analyzed using several techniques, data reduction, data presentation, conclusions or verification, as well as editing a script that will be used in the creation of movable pop-up book is. After analyzing the data, which have been collected are then found a creative concept that is used in the creation of movable pop-up book is that,